Analysis Of Motorcycle Effects To Saturation Flow Rate At Signalized Intersections In Malang City - Lila Kurnia W.; Achmad Wicaksono; M. Ruslin Anwar (Rekayasa Sipil, 2013)
For some signalized intersections in Malang City, visually can be seen that motorcycle is the dominant transportation mode. The research aims to know the influence of motorcycle to the characteristic of saturation flow at signalized intersections in Malang City by using Time Slice Method. The main focus of the research is to look at characteristic on first 6 seconds when the greentime period. The method used is Linear Regression with 3 classical assumption test. This study found that there are 66,04% approaches that have base saturation flow rate per effective width (S0/m) value in excess of IHCM 1997 standard (600 pcu/m), while 33,96% approaches still meets the IHCM 1997 standard. The mathematic model for the number of motorcycle at first 6 seconds (X) to Start Value (Y) is Y=-0,132+0,008X. There are proposed direction of design criteria to saturation flow in Malang City. First, review the Start Value based on influence of the number of motorcycle at first 6 seconds (X 1 ), effective width (X 2 ), and greentime (X ). From analysis obtained the model Y=0,003+0,020X 1 -0,128X 2 -0,012X . Second, review the Start Value based on influence of the number of light vehicle at first 6 seconds (X) to Start Value (Y). From analysis obtained the model Y=0,407+0,013X.